Effects of the neurotoxin β-N-methylamino-L-alanine (BMAA) on the early embryonic development of marine shellfish and fish - Yilei Fu; Aifeng Li; Aifeng Li; Jiangbing Qiu; Jiangbing Qiu; Wenhui Yan; Chen Yan; Lei Zhang; Min Li (Frontiers in Marine Science, 2022)
The neurotoxin β-N-methylamino-L-alanine (BMAA) produced by cyanobacteria and diatoms can accumulate in diverse aquatic organisms through the food web. In the present study, embryos of mussel Mytilus galloprovincialis (Lamarck, 1819), oyster Magallana gigas (Thunberg, 1793), and marine medaka Oryzias melastigma (McClelland, 1839) were exposed to BMAA dissolved in seawater and monitored for early developmental effects. Results demonstrated that the embryonic development of mussels and oysters were significantly inhibited when BMAA concentrations were above 100 μg BMAA·HCl/L (0.65 µM) and 800 μg BMAA·HCl/L (5.18 µM), respectively. The shell growth of mussel embryos was also markedly inhibited by BMAA ≥ 100 μg BMAA·HCl/L (0.65 µM). Based on the dose-response curves related to the modified malformation rate of embryos, the median effective concentration (EC50) values of mussel (48 h) and oyster (24 h) embryos were 196 μg BMAA·HCl/L (1.27 µM) and 1660 μg BMAA·HCl/L (10.7 μM), respectively. A sustained and dose-dependent decrease in heart rate was apparent in marine medaka embryos at 9-days post fertilization following BMAA exposure. However, no obvious effect on ATP concentration was noted in these marine medaka embryos. The current study contributes to our understanding of the sublethal effects of BMAA on the early embryonic development of marine bivalves and medaka. Further research examining the long-term effects of BMAA on the early development of marine organisms is necessary to determine seawater quality criteria for protection.